Monitoring Accessibility Services in Digital Television - Francisco Utray; Mercedes de Castro; Lourdes Moreno; Belén Ruiz-Mezcua (International Journal of Digital Multimedia Broadcasting)
This paper addresses methodology and tools applied to the monitoring of accessibility services in digital television at a time when the principles of accessibility and design are being considered in all new audiovisual media communication services. The main objective of this research is to measure the quality and quantity of existing accessibility services offered by digital terrestrial television (DTT). The preliminary results, presented here, offer the development of a prototype for automatic monitoring and a methodology for obtaining quality measurements, along with the conclusions drawn by initial studies carried out in Spain. The recent approval of the UN Convention on the Rights of Persons with Disabilities gives special relevance to this research because it provides valuable guidelines to help set the priorities to improve services currently available to users.